A systematic approach to Bronze corrosion products and the methods of treatment , applied on three bronze anklets from Dhamar museum , Yemen - Mohamed, Hazem (Archeomatica, 2014)
Three bronze anklets were found during the archaeological excavation of Yemeni mission 2002 A.D, in Gabal al- lawd , Jawf area , Yemen , they dated back to Minaean period in Yemen [sixth century B.C – 24 B.C] , and now they are situated in Dhamar regional museum .They were suffered from the deterioration aspects , two of these anklets had a thick corrosion products of pale green / brown , the third anklet had a rust-colored Black and Brown with the presence of small parts and scattered pale green. The aim of this paper is to examine, in detail, the corrosion of the selected objects that was grown during the long-term burial and identify its products that will help us to understand the corrosive factors and the degradation mechanisms , as well as their constituting metals in order to carry out scientific treatment and conservation . For this purpose ,samples from the objects were examined by Metallographic Microscope (ME) , Scanning Electron Microscope (SEM), the corrosion products were analyzed by X-ray diffraction (XRD) and X-ray fluorescence( XRF) was used to determine the objects metallic constituents . XRD data showed that the corrosion products constitute of cuprite , atacamite , and paratacamite , whereas XRF analysis declared that the anklets compose of bronze alloy . Microscopic examination reveals that the three anklets were suffered from the deterioration spots , which dispersed on the metal surface . Chemical cleaning was chosen for treating the objects , finally they were isolated to preserve them against further attack.